Readout-Segmented Echoplanar (RESOLVE) Diffusion-Weighted Imaging on 3T MRI in Detection of Cholesteatoma—Our Experience - Zaman, Sameeh Uz; Rangankar, Varsha P.; Krishnarjun, Muralinath; Kalekar, Tushar M.; Shah, Viraj Pankaj; Pawar, Rishikesh; Kulothungan, Gowtham (Indian Journal of Radiology and Imaging, 2023)
Background Several research studies have demonstrated the utility of diffusion-weighted imaging (DWI) in detecting middle ear cholesteatomas, especially with the non-echoplanar imaging (non-EPI) DWI technique. REadout Segmentation Of Long Variable Echo trains (RESOLVE), a multishot-EPI DWI, has better spatial resolution at a thinner section acquisition with reduced image distortion compared to the single-shot-EPI DWI technique.Purpose In this study, we evaluated the diagnostic ability of RESOLVE -DWI in middle ear cholesteatomas with surgical and histopathological support.Patients and Methods Fifty patients with clinical suspicion of primary cholesteatoma or postoperative recurrence were subjected to routine sequences and RESOLVE-DWI on magnetic resonance imaging (MRI). Thirty-eight patients had unilateral disease, while 12 patients had bilateral disease. The bilateral temporal bones of 50 patients were evaluated on MRI. The results attained by RESOLVE-DWI were correlated with intraoperative and histopathological findings.Results RESOLVE-DWI truly detected 55 of the 58 surgically proven cholesteatomas. RESOLVE-DWI could not detect three cholesteatoma lesions due to their small size and falsely diagnosed one case each of impacted wax and non-cholesteatomatous otitis media as cholesteatoma. With a 95% confidence interval, RESOLVE-DWI showed 94.8% sensitivity, 95.2% specificity, 96% positive predictive value, 93% negative predictive value, and 95% diagnostic accuracy in cholesteatoma detection.Conclusion RESOLVE-DWI is a sensitive and specific DWI technique for detecting middle ear cholesteatoma. However, RESOLVE-DWI has limitations in the diagnosis of small (<3 mm) cholesteatomas.
Keywords: cholesteatoma; hyperintense; keratin; MS-EPI; RESOLVE-DWI; sensitivity; specificity